Ключове регіональне звірення COOMET.AUV.A-K5. Аналіз результатів - Костеров, О. О.; Паракуда, В. В.; Kosterov, Oleksandr; Parakuda, Vasyl (Видавництво Львівської політехніки, 2019)
Проаналізовано результати двостороннього ключового регіонального звіряння COOMET.AUV.A-K.5 із калібрування однодюймових лабораторних еталонних мікрофонів у діапазоні частот від 2 Гц до 10 кГц. Звіряння здійснювали національні метрологічні інститути в галузі акустики України (ДП НДІ “Система”) та Польщі (GUM). Учасники надали результати вимірювання рівня та фази чутливості за тиском лабораторного еталонного дюймового мікрофона, який виконував роль еталона-переносника в цих звіряннях. На основі отриманих даних розраховано ступені еквівалентності результатів вимірювань ДП НДІ “Система” відносно відповідних опорних значень ключового звіряння консультативного комітету з акустики, ультразвуку та вібрації Міжнародного бюро з мір та ваг – CCAUV.A-K5, визнавши їх еквівалентними.

The article analyzes the results of bilateral key regional comparison COOMET.AUV.A-K.5 related to the calibration of one-inch laboratory standard microphones in the frequency range from 2 Hz to 10 kHz. The national metrology institutes in the field of acoustics of: Ukraine (DP NDI “Systema”) and Poland (GUM) have been participated in this comparison. The participants are presented the measurement results of the level and phase of the pressure sensitivity, as well as corresponding expanded uncertainty of measurements for the one-inch laboratory standard microphone, which in this case perform functions of the carrier-standard. On the basis of the obtained data, the stages of equivalence of the measurement results of DP NDI “Systema” were calculated in relation to the corresponding reference values, obtained during the key comparison of Consultative Committee for Acoustics, Ultrasound and Vibration of the International Bureau of Measures and Pounds – CCAUV.A-K5; it has been established that they are equivalent within the uncertainties declared by the participants. However, several comments were raised during by international experts while reviewing the obtained results. These comments mainly concern the effect of rather high measurement uncertainty of the pilot laboratory on the comparison results. The followed discussion revealed that the equivalence of the results of DP NDI “Systema” and CCAUV.A-K5 can be definitively established for all frequencies, excepting frequency 2 Hz while measuring the sensitivity level, and for all frequencies, but excluding the range 2– 4 kHz while measuring the sensitivity phase. For measurements at frequencies where it was impossible to reach an unambiguous conclusion on the equivalence of the obtained results, it was recommended to increase the declared uncertainty of measurements.
Key regional comparison COOMET.AUV.A-K5. Analysis of the results
Keywords: акустика; модуль та фаза чутливості за тиском; первинний метод взаємності; ключові звірення; непевність вимірювань; Acoustics; Modulus and phase of the pressure sensitivity; Primary method of reciprocity; Key comparison; Uncertainty of measurement